(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the derivational potentials of English and Russian words borrowed from Latin and Greek, focusing on morphological adaptations and patterns. It examines how these languages integrate classical roots, prefixes, and suffixes into their lexical systems, highlighting similarities and differences in derivational processes. The study employs a comparative analysis to identify structural and semantic transformations, offering insights into cross-linguistic influences and morphological productivity.